Cognitive Processing Therapy or Relapse Prevention for comorbid Posttraumatic Stress Disorder and Alcohol Use Disorder: A randomized clinical trial - Simpson, Tracy L.; Kaysen, Debra L.; Fleming, Charles B.; Rhew, Isaac C.; Jaffe, Anna E.; Desai, Sruti; Hien, Denise A.; Berliner, Lucy; Donovan, Dennis; Resick, Patricia A. (PloS one, 2022)
To compare a Posttraumatic Stress Disorder (PTSD) treatment (Cognitive Processing Therapy; CPT), an Alcohol Use Disorder (AUD) treatment (Relapse Prevention; RP), and assessment-only (AO) for those meeting diagnostic criteria for both PTSD and AUD. Participants with current PTSD/AUD (N = 101; mean age = 42.10; 56% female) were initially randomized to CPT, RP, or AO and assessed post-treatment or 6-weeks post-randomization (AO). AO participants were then re-randomized to CPT or RP. Follow-ups were at immediate post-treatment, 3-, and 12-months. Mixed effects intent-to-treat models compared conditions on changes in PTSD symptom severity, drinking days, and heavy drinking days. At post-treatment, participants assigned to CPT showed significantly greater improvement than those in AO on PTSD symptom severity (b = -9.72, 95% CI [-16.20, -3.23], d = 1.22); the RP and AO groups did not differ significantly on PTSD. Both active treatment conditions significantly decreased heavy drinking days relative to AO (CPT vs. AO: Count Ratio [CR] = 0.51, 95% CI [0.30, 0.88]; RP vs. AO: CR = 0.34, 95% CI [0.19, 0.59]). After re-randomization both treatment conditions showed substantial improvements in PTSD symptoms and drinking between pre-treatment and post-treatment over the 12-month follow-up period, with RP showing an advantage on heavy drinking days. Treatments targeting one or the other aspects of the PTSD/AUD comorbidity may have salutary effects on both PTSD and drinking outcomes. These preliminary results suggest that people with this comorbidity may have viable treatment options whether they present for mental health or addiction care. The trial is registered at clinicaltrials.gov (NCT01663337).